Triphenylbismuth(v) di[(iso)nicotinates] – transmetallation agents or divergent organometalloligands? First organobismuth(v)-based silver(i) coordination polymers. Issue 8 (31st January 2018) - Ben Kiran, Ahmad; Mocanu, Teodora; Pöllnitz, Alpár; Shova, Sergiu; Andruh, Marius; Silvestru, Cristian
Abstract : Ph3 BiX2 (X = O2 CC5 H4 N-4, O2 CC5 H4 N-3) as tectons connecting Ag(i ) cations; the selection of assembling species is required to avoid ligand exchange. Abstract : The reaction of Ph3 BiCl2 with alkali salts of isonicotinic and nicotinic acids afforded Ph3 Bi[O(O)CC5 H4 N-4]2 (1 ) and Ph3 Bi[O(O)CC5 H4 N-3]2 (2 ), respectively, which were characterized by multinuclear NMR spectroscopy in solution, mass spectrometry and IR spectroscopy in the solid state. Their molecular structures were established by single-crystal X-ray diffraction. For both1 and2 the molecules contain a trigonal bipyramidal C3 BiO2 core, with the phenyl groups in equatorial positions. The potential use of1 and2 as ditopic organometalloligands was investigated. The reaction of1 or2 with Me3 SnCl (1 : 2 molar ratio) resulted in carboxylato ligand exchange and the formation of Me3 Sn[O(O)CC5 H4 N-4] (3 ) and Me3 Sn[O(O)CC5 H4 N-3] (4 ) besides Ph3 BiCl2 . The crystals of both3 and4 contain 1-D coordination polymers built through intermolecular N → Sn interactions. The treatment of Ni[S2 P(O i Pr)2 ]2 with1 and2, respectively, resulted, in addition to di(carboxylato)nickel(ii ) derivatives, in isolation of Ph3 Bi and the disulphane [( i PrO)2 P(S)S]2 . New coordination polymers were obtained by reacting1 and2 with various silver(i ) salts: [Ag{Ph3 Bi[O(O)CC5 H4 N-4]2 }(OTf)] (5 ), [Ag{Ph3 Bi[O(O)CC5 H4 N-3]2 }(OTf)]·CH2 Cl2 (6 ·CH2 Cl2 ), [Ag{Ph3 Bi[O(O)CC5 H4 N-4]2 }](SbF6 )·2THF (7 ·2THF), [Ag{Ph3 Bi[O(O)CC5 H4 N-3]2 }](SbF6 )·CH2 Cl2 (8 ·CH2 Cl2 ) and [Ag{Ph3 Bi[O(O)CC5 H4 N-3]2 }(NO3 )]·CH2 Cl2 (9 ·CH2 Cl2 ). The crystal structures of5 and6 can be described as 1-D chains linked by triflate bridges in pairs of chains and 2-D networks, respectively. Compound7 features a 2-D grid-like topology of the network, with tecton1 acting as a tridentate ligand through both nitrogen and one oxygen atoms. The linker2 molecules adopt either cis (compound6 ) or trans (compounds8 and9 ) conformation. Complexes8 and9 are 1-D chain polymers exhibiting zig-zag and wavy motifs, respectively. The dimensionality of the structures is extended by the presence of supramolecular interactions (π⋯π, Ag⋯Ag, Ag⋯O).